'You just really have to assert yourself:' social work, nursing, and rehabilitation counseling student experiences of providing integrated behavioral health services before and after the immediate start of COVID-19 - Edward J. Alessi; Barbara Caldwell; Anthony S. Zazzarino; Brett Greenfield; Patricia A. Findley (BMC, 2022)
Abstract Background Educators who train healthcare students to provide behavioral health services in primary care settings frequently encounter challenges as they work to ensure that students acquire the knowledge and skills to effectively function on interprofessional practice teams. This has become increasingly important during COVID-19, as interprofessional collaborative practice is needed more than ever to address the interrelated health, mental health, and social structural issues linked to the pandemic. Methods We used qualitative focus groups to understand the experiences of 6 interprofessional teams (comprised of graduate social work, nursing, and rehabilitation counseling students; n = 19) providing behavioral health services in primary care settings before and after the immediate start of COVID-19. To triangulate data and enrich findings, one focus group with students' faculty supervisors was also conducted; n = 5). Data were analyzed using thematic analysis. Results Four themes highlighted student participants' need to assert themselves at the beginning of their educational experience, to communicate and learn from one another to develop positive team dynamics, to contend with role confusion and missed opportunities for collaboration, and to manage the emotional impact of COVID-19 on learning. Conclusion Findings indicate that educators should work with clinical faculty and agency supervisors to orient students to ensure they have role clarity within the agency. Graduate students providing behavioral health services should also learn to work collaboratively within their scopes of practice to serve patients virtually, especially in preparation for public health emergencies.